Impact of late-onset group B streptococcus infection on families: An observational study. (January 2021) - Raybould, Grace; Plumb, Jane; Stanley, Alison; Walker, Kate F.
Highlights: The majority of parents had not heard about group B Strep (GBS) before their child developed late-onset GBS (LOGBS) infection. The majority reported that their own or their close relatives' mental health suffered. A significant minority reported financial difficulty because of their baby's LOGBS infection. Most participants reported that they experienced practical difficulties during their baby's inpatient stay. The majority experienced problems with planning or reduced enjoyment of subsequent pregnancies. Abstract: Objectives: Understand the parental impact of having a baby affected by late-onset group B Strep (LOGBS) infection. Understand the social, mental and financial impact on parents/carers or family members of those affected by LOGBS infection. Investigate family information needs and experiences of information provided. Study design: We devised a 57-item online survey, composing of binary and matrix questions and free text answers. The survey was distributed internationally to families with a baby(ies) affected by LOGBS infection. The questionnaire was designed as a collaborative effort by Group B Strep Support, its medical advisory panel members, midwives, neonatologists, parents and volunteer analysts. Data were collected from June to September in 2018. Results: 531 participants responded. 252 babies (55 %) made a full recovery from their LOGBS infection, 145 (32 %) recovered with long term sequelae and 61 (13 %) died. 126 respondents (32 %) felt there was a minor to substantial impact on their child's day to day life as a consequence of LOGBS infection. 343 respondents (69 %) had not heard about GBS before their child developed LOGBS infection. 338 respondents (77 %) did not receive an information leaflet on GBS. As a result of their child's LOGBS infection, 177 respondents (39 %) experienced either minor or substantial financial difficulty and 314 respondents (70 %) felt that their own or a family member's mental health was affected. 300 respondents (66 %) experienced problems with planning or reduced enjoyment of subsequent pregnancies. 102 respondents (29 %) reported their other children experienced difficulty due to their sibling's LOGBS infection. Conclusions: The results of our study provide a novel insight into families' experiences following a baby affected by LOGBS infection. Study findings suggests that families suffer significant financial and psychological difficulties as a result of LOGBS infection. Furthermore, information needs are frequently being left unmet.